2015
DOI: 10.1177/1535370215615699
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of immune-related genes in leukocytes of patients with diagnosed gestational diabetes mellitus (GDM)

Abstract: Compelling evidence indicates that the immune system is linked to metabolism in gestational diabetes mellitus (GDM), but factors participating in these processes still are awaiting identification. Inducible nitric oxide synthase, encoded by the NOS2 gene, and surfactant protein D, encoded by the SFTPD gene, have been implicated in diabetes. We investigated NOS2 and SFTPD mRNA levels in leukocytes obtained from 125 pregnant women with (n ¼ 87) or without (control group; n ¼ 38) GDM, and, in turn, correlated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…The current study demonstrated that glycyrrhizic acid significantly downregulates the protein expression levels of p38MAPK in MTX-induced enteritis. Additionally, several other previous studies demonstrated that glycyrrhizic acid attenuates glycative stress in the kidneys of diabetic mice through suppression of NF-κB and p-p38MAPK (21,43). These data support the hypothesis that the anti-inflammatory effects of glycyrrhizic acid may be associated with p38MAPK signaling.…”
Section: A B C D a Bsupporting
confidence: 84%
“…The current study demonstrated that glycyrrhizic acid significantly downregulates the protein expression levels of p38MAPK in MTX-induced enteritis. Additionally, several other previous studies demonstrated that glycyrrhizic acid attenuates glycative stress in the kidneys of diabetic mice through suppression of NF-κB and p-p38MAPK (21,43). These data support the hypothesis that the anti-inflammatory effects of glycyrrhizic acid may be associated with p38MAPK signaling.…”
Section: A B C D a Bsupporting
confidence: 84%
“…Therefore, the primary goal for successful medical management of GDM is to maintain the concentration of maternal blood glucose, particularly postprandial blood glucose levels, within the ideal range (10). It has been hypothesized that the mechanism of GDM involves an increase in the hormones produced by the placenta known to resist insulin, which results in a decreased sensitivity to insulin in pregnant women (11,12). This consolidates the scientific basis of medical nutrition therapy for the treatment of GDM (13).…”
Section: Introductionmentioning
confidence: 97%
“…Our findings show that progeny of experimental gestational diabetes mellitus (EGD) rats have such immune violations of immunological tolerance as AIRE gene repression, reduced mRNA levels of Deaf1, transcription factor Foxp3, the latter being confirmed by decrease in Тreg cells [1] and inhibition of gene expression suppressor cytokine IL-10 and negative costimulatory molecules Ctla4 [2]. However, gestational diabetes (GD) increases the genes expression of immune response in pregnant [3] and leads to violations of innate and adaptive components of immune system in progeny. Thus, Li Q. et al (2016) showed that gestational diabetes mellitus increased interleukin-1β in progeny spleen cells [4].…”
Section: ключові словаmentioning
confidence: 99%